Answer:
k = -
, k = 2
Step-by-step explanation:
Using the discriminant Δ = b² - 4ac
The condition for equal roots is b² - 4ac = 0
Given
kx² + 2x + k = - kx ( add kx to both sides )
kx² + 2x + kx + k = 0 , that is
kx² + (2 + k)x + k = 0 ← in standard form
with a = k, b = 2 + k and c = k , thus
(2 + k)² - 4k² = 0 ← expand and simplify left side
4 + 4k + k² - 4k² = 0
- 3k² + 4k + 4 = 0 ( multiply through by - 1 )
3k² - 4k - 4 = 0 ← in standard form
(3k + 2)(k - 2) = 0 ← in factored form
Equate each factor to zero and solve for k
3k + 2 = 0 ⇒ 3k = - 2 ⇒ k = - ![\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
k - 2 = 0 ⇒ k = 2
Answer:
0.65
5.16
6.5
6.51
31.56
Step-by-step explanation:
Answer:
9
Step-by-step explanation:
If your looking looking for the y-intercept its y=-3
I don't really understand what you are asking though....
The tree is 20 m tall .
Step-by-step explanation:
<h2>Given : </h2>
- 2m tall tree cast a shadow 4 m long .
=> 2 m tree = 4 m long
If we find shadow of 1 m tall tree = 4/2
=> we have to find height of 10 m tall tree which is .. = 4/2 × 10 = > 20 m